Limnonema gen. nov. (Aerosakkonemataceae, Cyanobacteria): Two Novel Species from Republic of Korea Characterized by Morphological and Molecular Analyses - Ji-Ho Song; So-Won Kim; Nam-Ju Lee; Do-Hyun Kim; Hye-Ryeung Wang; Ok-Min Lee (Diversity, 2023)
In this study, 18 strains of cyanobacteria were isolated from seven sites, including the Han River and Anseong Stream in Republic of Korea, and we propose these isolated strains as Limnonema gen. nov., belonging to the Aerosakkonemataceae family of the Oscillatoriales order, and also, as L. hangangris sp. nov. and L. anseonga sp. nov. These strains were identified based on morphological data using a light microscope and a transmission electron microscope, and molecular data using 16S rRNA and 16S–23S ITS gene sequences. The genus Limnonema was mainly collected as planktons, and some L. hangangris (ACKU-695–697) appeared as epilithic cyanobacteria. The genus Limnonema showed filamentous trichomes, intracellular gas vacuoles, and irregular thylakoids arrangement, which was distinct from genera Cephalothrix, Microseira, and Potamosiphon belonging to the family Aerosakkonemataceae. Moreover, the cell widths of genus Limnonema were narrower than those of genus Aerosakkonema, which is the type genus of the family Aerosakkonemataceae, and L. anseonga contained more cells with wider widths than those of L. hangangris. In the 16S rRNA gene sequence phylogeny, genus Limnonema belonged to the family Aerosakkonemataceae and was distinguished from its close relatives, genera Aerosakkonema and Cephalothrix, and L. hangangris and L. anseonga formed different branches. In 16S rRNA gene sequence similarity, genus Limnonema showed 95.4–95.9% and 93.6–94.4% similarity with genera Aerosakkonema and Cephalothrix, respectively, and L. hangangris and L. anseonga showed 97.6–97.7% similarity between each other. In the 16S–23S ITS secondary structure, the D1–D1′, Box-B, and V3 helices of genus Limnonema were distinguished from genera belonging to the family Aerosakkonemataceae, and the V3 helices of L. hangangris and L. anseonga were also different from each other.